Business-oriented enterprise integration for organizational agility - Qiu, Robin G. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book explores technical integration challenges with a focus on identifying a viable solution on how to enable rich, flexible, and responsive information links, in support of the changing business operations across organizations"--Provided by publisher.